Feasibility and accuracy of targeted axillary dissection in breast cancer patients; single center experience - Kaya, Cemal; Burcu, Büşra; Çetinoğlu, Işık; Uçak, Ramazan; Çerekçi, Esma; Şahin, Cennet; Demircioğlu, Zeynep Gül; Şener, Aziz; Halil, Süleyman (Frontiers in Surgery, 2024)
Introduction: Axillary complete response (pCR) was observed in approximately half of breast cancer patients who received neoadjuvant chemotherapy (NAC) due to axillary positivity. Preventing axillary morbidity due to unnecessary axillary lymph node dissection (ALND) is extremely important for patients' quality of life. Targeted axillary dissection (TAD) is a technique developed to improve axillary staging and reduce the false negative rate in sentinel lymph node biopsy.Methods: Patients with cN1-N2 (clinically node) breast cancer whose axillary lymph node metastasis was confirmed by biopsy and who received NAC marked with a clip were included in the study. Patients who achieved clinical response after systemic treatment underwent sentinel lymph node biopsy (SLNB) with additional methods such as methylene blue guided dissection, skin marking for clip on lymph node (CLN) localization, and wire guided with imaging excision of the CLN. TAD and ALND pathology results were evaluated and analyzed with patient and tumor characteristics.Results: 83 patients who met the eligibility criterias for the study were examined retrospectively. 21 of the patients underwent TAD alone, and 62 patients underwent ALND after TAD. CLN rate was 98.8% in patients underwent only TAD and this rate was increased to 100% in patients underwent ALND after TAD. FNR in SLN, CLN, and TAD were 28.6%, 10.7%, and 3.6%, respectively. Conclusion: TAD is a feasible and reliable surgical approach to detect axillary residual disease with a high success rate.